Influence of Political Stability on Foreign Direct Investment (FDI) Inflows in Nigeria - Ajimobi, Lucas (American Journal of Finance, 2024)
Purpose: The aim of the study was to assess the influence of political stability on foreign direct investment (FDI) inflows in Nigeria. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study indicated that political stability significantly influences foreign direct investment (FDI) inflows, as investors seek environments where their investments are secure and can yield predictable returns. Stable political conditions reduce risks related to government policy changes, expropriation, and civil unrest, thereby attracting more FDI. Conversely, political instability, marked by frequent government changes, corruption, and social unrest, deters investors due to increased uncertainty and risk. Studies have shown that countries with stable political climates tend to receive higher FDI inflows as they offer a safer, more predictable investment environment. Additionally, strong institutions and good governance practices further enhance investor confidence, leading to sustained economic growth through increased foreign investment. Implications to Theory, Practice and Policy: Institutional theory, risk theory and eclectic paradigm may be used to anchor future studies on assessing the influence of political stability on foreign direct investment (FDI) inflows in Nigeria. In practical terms, businesses and investors should focus on strengthening political institutions to create a stable and predictable environment. Policymakers play a crucial role in creating an environment conducive to FDI by prioritizing the implementation of political reforms that enhance stability. Ensuring free and fair elections, protecting civil liberties, and promoting effective governance structures are vital steps in this direction.